Trapped fools : thirty years of Israeli policy in the Territories - Gazit, Shlomo (Cass series--Israeli history, politics, and society, 2003)
Based upon the author's own experiences this study explores the Israeli government's attitude to the West Bank and Gaza over a period of 30 years. The ""fools"" in the book's title refers not only to the Arabs who rejected Israeli peace offers but to the Israelis themselves.